Prebiotic Beyond Immunity: Benefits on Children’s Physical and Cognitive Growth - Jatiningrum Muaris, Hindah; Stephanie Kartjito, Melissa; Fadil Himawan, Muhamad (Ridwan Institute, 2024)
Prebiotics have long been known to play an important role in supporting the immune system, especially in children. However, recent research shows that the benefits of prebiotics are not limited to increasing immunity. Prebiotics also have a positive impact on children's physical and cognitive growth. This study aims to identify and analyze the benefits of prebiotics on children's physical growth and cognitive development. This study uses a qualitative research method. The data collection technique in this study was through literature studies. The data that has been collected was then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. Research shows that prebiotics play a role in supporting children's physical growth by improving nutrient absorption and supporting healthy bone development. In addition, prebiotics also have an important role in improving cognitive function. The relationship between gut health and the brain is increasingly recognized, with recent research stating that the condition of the gut microbiota can affect cognitive health. Beneficial bacteria that receive prebiotic intake can produce compounds that can cross the blood-brain barrier, affecting cognitive functions such as memory, learning, and concentration.